2018
DOI: 10.1289/ehp3423
|View full text |Cite
|
Sign up to set email alerts
|

Critical Windows for Associations between Manganese Exposure during Pregnancy and Size at Birth: A Longitudinal Cohort Study in Wuhan, China

Abstract: Background: Prenatal overexposure to manganese (Mn), an essential micronutrient, is related to impaired fetal growth and development. Fetuses appear to be highly sensitive to Mn during short periods of gestation. However, little is known about the critical windows of susceptibility to Mn for humans. Objectives: Our objective was to estimate trimester-specific associations of exposure to Mn with size at birth. Methods: Urine samples of 3,022 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 53 publications
(64 reference statements)
0
15
0
Order By: Relevance
“…55 Several investigations have suggested significant and strong relationships between exposure to environmental pollutants (e.g., bisphenols, arsenic) in the third trimester and birth outcomes, while null or weaker associations were observed in other trimesters. 56,57 More studies should be done to validate our results.…”
Section: Discussionmentioning
confidence: 71%
“…55 Several investigations have suggested significant and strong relationships between exposure to environmental pollutants (e.g., bisphenols, arsenic) in the third trimester and birth outcomes, while null or weaker associations were observed in other trimesters. 56,57 More studies should be done to validate our results.…”
Section: Discussionmentioning
confidence: 71%
“…We constructed GA-specific standard deviation scores (z-scores) for fetal growth parameters based on both ultrasound and birth measures using the GAMLSS package in R software. , Briefly, we modeled AC, HC, BPD, FL, and fetal weight (EFW and birth weight combined) using a cubic spline by GA in days based on our study population after normalizing the parameters using Box–Cox transformations. The fetal growth z-scores were acquired based on the best-fitting models according to Akaike’s information criteria, which represented the percentile of the fetal or birth size at any specific GA …”
Section: Methodsmentioning
confidence: 99%
“…34,35 Briefly, we modeled AC, HC, BPD, FL, and fetal weight (EFW and birth weight combined) using a cubic spline by GA in days based on our study population after normalizing the parameters using Box−Cox transformations. The fetal growth z-scores were acquired based on the bestfitting models according to Akaike's information criteria, which represented the percentile of the fetal or birth size at any specific GA. 36 Covariates. At recruitment, we obtained basic characteristics of study participants via self-reported questionnaire, which included age, height, marital status, education level, income, geographic residence setting, sources of drinking water, and reproductive history.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The exposure to high levels of Mn may be associated not only with neurological disorders such as Alzheimer's disease, Parkinson's disease and Huntington's disease [3][4][5] , but also, consumption of Mn-contaminated water impacts on children's neurodevelopment triggering changes in the intelligence quotient (IQ) and producing attention-deficit hyperactivity disorders 6,7 . Furthermore, the overexposure to Mn during pregnancy leads to significant reductions in size, length and weight of newborns 8 .…”
Section: Introductionmentioning
confidence: 99%